1楼:匿名用户
^in=∫
(tanx)^ndx
=∫(tanx)^(n-2)×tanxdx
=∫(tanx)^(n-2)×(1/cosx-1)dx
=∫((tanx)^(n-2)×1/cosx-(tanx)^(n-2))dx
=∫(tanx)^(n-2)×1/cosxdx-∫(tanx)^(n-2)dx
=∫(tanx)^(n-2)dtanx-∫(tanx)^(n-2)dx
=(tanx)^(n-1)/(n-1) -i[n-2]
∵i1=∫tanxdx=∫sinx/cosx dx=∫-dcosx/cosx=-ln|cosx|+c
∴∫(tanx)^5dx
=i5=(tanx)^4/4-i3
=(tanx)^4/4-(tanx/2-i1)
=(tanx)^4/4-tanx/2+i1
=(tanx)^4/4-tanx/2-ln|cosx|+c
设I(nsinx)ndx试证Inn-1)n)(In-2)
1楼 匿名用户 i n sinx ndx sinx n 1 sinxdx sinx n 1 d cosx sinx n 1 cosx cosxd sinx n 1 sinx n 1 cosx n 1 cos x sinx n 2 dx sinx n 1 cosx n 1 1 sin x sinx n...
设a,b,c R+,求证a2+b22)
1楼 不离不弃 a b 2 0则a 2 b 2 2ab 即2 a 2 b 2 a 2 2ab b 2即2 a 2 b 2 a b 2 即a 2 b 2 a b 2 2 即 a2 b2 2 2 a b 设a,b,c r,且a b c 2,a2 b2 c2 12,则c的最大值和最小值的差为163163 ...
设a、b、c R,求证(a+b,设a、b、c∈R,求证√(a+b)+√(b+c)+√(c+a)≥√2(a+b+c)
1楼 陈 因为容易证明 a b a b 2 b c b c 2 c a c a 2 所以三个加起来,得到 a b b c c a 2 a b c 已知a b c r a b c 求证a 2 b 2 c 2 2abcosc 2bccosa 2accosb 2楼 匿名用户 a b c ,是三 角形的内角...